2007
DOI: 10.1007/s00213-007-0722-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of tryptophan depletion on the attentional salience of smoking cues

Abstract: Acutely compromising central serotonergic neurotransmission via ATD heightens the attentional salience of cigarette-related cues, perhaps by triggering reward and motivational deficits underlying nicotine dependence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 53 publications
0
11
0
1
Order By: Relevance
“…One explanation for these unexpected findings is that the effects of nicotine depend upon attentional salience (Hitsman, Spring, Pingitore, Munafò, & Hedeker, 2007) as well as the emotional valence of the stimulus such that nicotine enhances attention to stimuli with greater salience and with greater positive valence given equivalent salience (Gilbert, Rabinovich et al, 2008). Alternatively, these results may hinge on the failure to find priming effects for this dual-picture condition independently of nicotine; the positive primes failed to promote increased first-gaze bias towards happy rather than neutral stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…One explanation for these unexpected findings is that the effects of nicotine depend upon attentional salience (Hitsman, Spring, Pingitore, Munafò, & Hedeker, 2007) as well as the emotional valence of the stimulus such that nicotine enhances attention to stimuli with greater salience and with greater positive valence given equivalent salience (Gilbert, Rabinovich et al, 2008). Alternatively, these results may hinge on the failure to find priming effects for this dual-picture condition independently of nicotine; the positive primes failed to promote increased first-gaze bias towards happy rather than neutral stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…The present study proposes a G*E model of smoking habits involving a functional variation of a gene (5-HT), which has direct implications on serotonergic neurotransmission (35). …”
Section: Discussionmentioning
confidence: 99%
“…Booij et al (2005) tested participants' abilities to name the colours of emotionally loaded words and found that ATD increased interference for positively loaded words only. In another study, participants named the colours of emotionally loaded words and smoking-related words in smokers with or without histories of depression (Hitsman et al, 2007). ATD increased interference times for all types of words irrespective of psychiatric history.…”
Section: Selective or Focused Attentionmentioning
confidence: 98%